Almost Periodic Solutions for Wilson-Cowan Type Model with Time-Varying Delays - Shasha Xie; Zhenkun Huang (Discrete Dynamics in Nature and Society)
Wilson-Cowan model of neuronal population with time-varying delays is considered in this paper. Some sufficient conditions for the existence and delay-based exponential stability of a unique almost periodic solution are established. The approaches are based on constructing Lyapunov functionals and the well-known Banach contraction mapping principle. The results are new, easily checkable, and complement existing periodic ones.